The Effect of Hexanoyl Glycol Chitosan on the Proliferation of Human Mesenchymal Stem Cells - Jeong, Young-Hoon (Polymers (Basel), 2018)
Adipose-derived mesenchymal stem cells (AD-MSCs) have been studied as desirable cell sources for regenerative medicine and therapeutic application. However, it has still remained a challenge to obtain enough adequate and healthy cells in large quantities. To overcome this limitation, various biomaterials have been used to promote expansion of MSCs in vitro. Recently, hexanoyl glycol chitosan (HGC) was introduced as a new biomaterial for various biomedical applications, in particular 3D cell culture, because of its biodegradability, biocompatibility, and other promising biofunctional properties. In this study, the effect of HGC on the proliferation of AD-MSCs was examined in vitro, and its synergistic effect with basic fibroblast growth factor (bFGF), which has been widely used to promote proliferation of cells, was evaluated. We found that the presence of HGC increased the proliferative capacity of AD-MSCs during long-term culture, even at low concentrations of bFGF. Furthermore, it suppressed the expression of senescence-related genes and improved the mitochondrial functionality. Taken all together, these findings suggest that the HGC demonstrate a potential for sustained growth of AD-MSCs in vitro.